Interactive effect of moisture restriction and salicylic acid on biochemical responses in Phaseolus coccineus - Aguilar-Luna, Jesús Mao; Loeza-Corte, Juan Manuel; Díaz-López, Ernesto (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The increase in water scarcity leads to consider the understanding of staple crops under these conditions, coupled with this, the positive responses of salicylic acid in different crops, may be an option in bringing to fruition the cultivation of runner bean (Phaseolus coccineus). This study evaluated the effect of salicylic acid (SA) on the biochemical responses in P. coccineus, with humidity restriction in the periods from January to July 2019 and 2020, at the Benemerita Autonomous University of Puebla, Mexico. The research consisted of three levels of drought: 30, 60 and 100% soil moisture; five levels of SA: 0, 0.5, 1.0, 1.5 and 2.0 mM; and two levels of fertilization: non-fertilizer and fertilizer [(00-60-30) at sowing + (30N) foliar nitrogen at grain filling stage] for the two growing periods. The experimental design was in factorial random blocks with five replications. The results showed that the foliar application with 1.5 mM of SA maintained the highest relative water content in leaves (89.05%), as well as chlorophyll a, b and carotenoids (2.20, 1.11 and 0.90 µg.mL-1, respectively); of glycinebetaine (24.80 µmol.g-1 DW) and total soluble sugars (31.15 mg eq.glucose g-1 DW), excluding proline. The SA did not increase the protein fractions, even in plants with fertilizer; but the positive effects of SA were greater in plants without hydric stress and with fertilization.